Impact of brick kilns' emission on soil quality of agriculture fields in the vicinity of selected Bhaktapur area - Suwal, Gajendra Bhakta (Journal of Science and Engineering, 2018)
The study was conducted to evaluate the impact of brick kilns' on different physiochemical parameters of soils of agricultural field, located in the vicinity of Bhaktapur. The study was carried out by measuring the pH value and the micro nutrients of the soil. During the entire study period, the pH of soil near brick kiln was measured to be 5.5 and as distance increased the pH of soil was recorded up to 6.9 which mean the soil was acidic near the kiln and was neutral farther away. The findings revealed that the pH value was high and nutrient content were deficient in soil at 50 m while increasing gradually at distances of 100 m and 150 m it was found opposite of it. It signifies that the quality of soil increases proportionally to the distance from the brick kiln area. Similarly, the micro nutrients like organic matter are also increased with increasing distance.